I love you because you$1 (Bre yous - Baker, Liza.; McPhail, David, 1940- (New York : Scholastic, 2001)
Describes, in rhyming text and illustrations, a mother$1 (Bs love for her child no matter how he feels or what he does.s
"Cartwheel Books."
Keywords: Mother and child -- Fiction; Love -- Fiction; Foxes -- Fiction; Stories in rhyme